Decolorization and detoxification of synthetic azo dye wastewater by Enterobacter hormaechei MW584986 isolated from textile wastewater - Echejiuba , Jude Chinwendu; Ogugbue , Chimezie Jason; Obuekwe, Ifeyinwa Sarah (Macedonian Journal of Ecology and Environment, 2024)
Biotreatment of textile wastewater is a viable option and a promising strategy for its detoxification before its discharge into the environment. This study evaluated the ability of Enterobacter hormaechei isolated from textile wastewater to decolorize (degrade) trypan blue. It also identified and optimized conditions affecting both color removal and degradation processes of trypan blue using Central Composite Design (CCD) of Response Surface Methodology (RSM). Subsequently, Micro-toxicity assay was used to evaluate the detoxification of the dye by Enterobacter hormaechei, while generated metabolites were ascertained based on Chromatography-Mass Spectrophotometer analysis. Enterobacter hormaechei MW584986 effectively decolorized trypan blue synthetic dye wastewater within 24 h of incubation at 77.5% from the initial trypan blue concentration of 100 mg/L. Optimal conditions for maximum decolorization efficiency were determined to be pH 7.0, temperature 35°C, salinity 5‒7 g/L and glucose concentration of 10 g/L. Micro-toxicity test showed significant growth rate of Chlorella vulgaris in treated broth relative to the untreated sample at same concentration, indicating the breakdown of the compound into less toxic substances. GC-MS analyses of the decolorized broth showed degradation of azo dye into simpler substances by Enterobacter hormaechei MW584986. This study thus reports an efficient, cheap and environmentally safe textile wastewater treatment strategy.